The Effectiveness of Local Culture-Integrated Science Learning through Project-Based Assessment on Scientific Attitudes and Science Process Skills of Elementary School Students - Parmiti, D. P.; Rediani, N. N.; Antara, I. G. W. S.; Jayadiningrat, M. G. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
This study aims to analyze the effect of project-based assessment based on local culture on students' scientific attitudes and science process skills in science learning in elementary schools. This research is a quasi-experimental study with a non-equivalent post-test-only control group design. The population in this study was 151 participants, while the sample selected through random sampling technique was 61 participants divided into two classes. The data collection methods in this research were test and non-test methods. The instruments used were scientific attitude questionnaires and performance tests, and observation sheets. A validation process measured the validity and reliability of the instrument. The data obtained were analyzed using the MANOVA test assisted by the IBM SPSS Statistics 21.0 application. The hypothesis test results show a significance value of 0.003 (Sig <0.05) so that Ho is rejected and Ha is accepted. Thus, it can be concluded that there are simultaneous effects in scientific attitudes and science process skills between students’ learning with local culture-based Project-based Assessment and students’ learning with conventional assessment applied.